LAS FUENTES DEL DERECHO DEL TRABAJO - Pacheco Zerga, Luz (Revista de Derecho, 2020)
The application of Labor Law requires, as in other legal disciplines, knowledge of the sources that allow to delimit the scope of rights in conflict situations. Not all sources have the same incidence in this application, so it is interesting to compile those that are common to the rest of the legal system and highlight those of this specialty. Consequently, a brief description of each of them is made, placing them at the level that corresponds to them in the normative hierarchy, highlighting some incongruities that exist in their application, as well as the opinions of the most authoritative iberoamerican academic doctrine. The sources analyzed, emphasizing those with the highest incidence in Labor Law, are ten: the Constitution, international treaties, the judgments of the Constitutional Court, the laws, the regulations of the laws, the regulations of the administrative authority, the Internal Regulations Health and Safety at Work, the Internal Work Regulations, ordinary jurisprudence, and custom. The role played by the employment contract in the source system is also revealed. Finally, it is concluded by placing the list of applicable sources in the field of Labor Law for the consideration of legal operators, highlighting the particularities of some of them. The methodology used has been qualitative, inductive-analytical.